Short-Chain Naphthoquinone Protects Against Both Acute and Spontaneous Chronic Murine Colitis by Alleviating Inflammatory Responses - Shastri, Sonia; Shinde, Tanvi; Woolley, Krystel L.; Smith, Jason A.; Gueven, Nuri; Eri, Rajaraman (Frontiers in Pharmacology, 2021)
Ulcerative Colitis (UC) is characterised by chronic, relapsing, idiopathic and multifactorial colonic inflammation. Recent evidence suggests that mitochondrial dysfunction plays a critical role in the onset and recurrence of this disease. Previous reports highlighted the potential of short chain quinones (SCQs) for the treatment of mitochondrial dysfunction due to their reversible redox characteristics. We hypothesised that a recently described potent mito-protective SCQ (UTA77) could ameliorate UC symptoms and pathology. In a dextran sodium sulphate (DSS)- induced acute colitis model in C57BL/6J mice, UTA77 substantially improved DSS-induced body weight loss, disease activity index (DAI), colon length and histopathology. UTA77 administration also significantly increased the expression of tight junction proteins occludin, and zona-occludin 1 (ZO-1), which preserved intestinal barrier integrity. Similar responses were observed in the spontaneous Winnie model of chronic colitis, where UTA77 significantly improved DAI, colon length and histopathology. Furthermore, UTA77 potently suppressed elevated levels of pro-inflammatory cytokines and chemokines in colonic explants of both DSS-treated and Winnie mice. These results strongly suggest that UTA77 or its derivatives could be a promising novel therapeutic approach for the treatment of human UC.